Relationship of independence of internal audit and internal audit capability (IACM) in the Malaysian public sector organizations - Hasnah, Haron; Ishak, Ismail; Ibrahim, Daing Nasir; Darun, Mohd Ridzuan; Mahmud, Fatimah (2019)
The purpose of this study is to examine the importance of internal audit capability in enhancing the performance of Malaysian public sector organizations. The structure of public sector organization in Malaysia comprises of several level and types of organizations which lead to the complexity of the structure. Therefore, it requires a comprehensive procedure and guidelines especially in financial management. According to the Auditor General, internal audit function plays a proactive role as a monitoring mechanism and in examining ongoing projects. It may assist public sector entities in achieving their objectives effectively, efficiently, economically and ethically by providing unbiased and objective assessments. The objectives of this study is to determine the level of the internal audit capability in the Public Sector Organizations and to determine the relationship of independence of internal auditor and the level of internal audit capability of Malaysian public sector organizations. Questionnaires were sent to head of internal auditors in the list given by the National Audit Department. Only 70 responses were received and analyzed for descriptive statistics and relationship testing using SPSS and SmartPLS. It was found that 47 organizations were only at capability Level 1 - Initial while remaining 13 organizations scored capability Level 2 Infrastructure. People Management Dimension is the most crucial issue to be attended (lack of skilled and competence internal audit staffing). It was also found that independence of internal audit unit has a positive and significant influence on overall internal audit capability level